Fictions of the Modern Architectural Narrative: An Epistemological Construct of Oppositions and Discontinuities - Okem, Selim (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2015)
The research presented here questions the possibility of drawing an outline of the structure of modern architectural knowledge, and how the concepts of 'discontinuity' and 'opposition' could be utilized in attaining an epistemological reading of such an outline. A contextual analysis of texts and visual material provides compatible data on how oppositions could form the basis of a late modern architectural episteme. The method of the research includes classification of these texts and visual content and an interpretive study of the classified visual material to determine the major oppositions in modern architectural discourse. Along with this non-reactive contextual research method, a close-ended survey was conducted among a sample of architectural students to evaluate the epistemological value of these oppositions. Findings of this research showed that, in part, the oppositions (being a derivative of the notion of discontinuity) were what made modern architectural knowledge impartible (teachable), legible (readable) and permeable (absorbable, expressible).
Keywords: Architectural narrative; discontinuity; field condition; index architecture; modern architectural episteme; opposition; Architecture